Die postmodernistiese diskoers en die Suid-Afrikaanse ekonomiese oorgang - Naude, Willem (University of the Free State, 1999)
The postmodernist reaction to the Cartesian Anxiety caused by the rejection of modernism as philosophical basis for science is set out in this paper. It is argued that the hermeneutical tradition within postmodernism might be a useful way of approaching the current question of an appropriate economic strategy for the postapartheid economy. Some implications that might be relevant for the role of economists at South African Higher Education Institutions (HEls) are drawn out. The paper concludes that discourse, debate and rhetoric might be indispensable for the advance of economic justice in South Africa, and might also be an instrument to allow for individual choice, and eventually, individual reckoning.

Hierdie artikel beskryf die postmodernistiese reaksie op die verwerping van modernisme in die wetenskap en poog om die implikasies daarvan vir die ekonomiese wetenskap te identifiseer. Die beskouinge van die hermeneutiese skool van die postmodernisme mag moontlik nuttig vertolk word gegewe die noodsaaklikheid van 'n algemeen aanvaarde ekonomiese ontwikkelingstrategie vir postapartheid Suid-Afrika. 'n Implikasie vir die beoefening van die ekonomiese wetenskap aan hoër onderwysinstellings in Suid-Afrika is dat debat, diskoers en retoriek onontbeerlik mag wees vir die bevordering van ekonomiese besluitnemingen bestuur.
Keywords: Postmodernistic discourse; South Africa; Economic transition; Cartesian Anxiety; Higher education institutions